If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -10) = 5(4 + -3y) + -14 Reorder the terms: 3(-10 + y) = 5(4 + -3y) + -14 (-10 * 3 + y * 3) = 5(4 + -3y) + -14 (-30 + 3y) = 5(4 + -3y) + -14 -30 + 3y = (4 * 5 + -3y * 5) + -14 -30 + 3y = (20 + -15y) + -14 Reorder the terms: -30 + 3y = 20 + -14 + -15y Combine like terms: 20 + -14 = 6 -30 + 3y = 6 + -15y Solving -30 + 3y = 6 + -15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15y' to each side of the equation. -30 + 3y + 15y = 6 + -15y + 15y Combine like terms: 3y + 15y = 18y -30 + 18y = 6 + -15y + 15y Combine like terms: -15y + 15y = 0 -30 + 18y = 6 + 0 -30 + 18y = 6 Add '30' to each side of the equation. -30 + 30 + 18y = 6 + 30 Combine like terms: -30 + 30 = 0 0 + 18y = 6 + 30 18y = 6 + 30 Combine like terms: 6 + 30 = 36 18y = 36 Divide each side by '18'. y = 2 Simplifying y = 2
| 7-y-y=?1 | | 15x+45=11 | | 3-7(2x-3)= | | 2m=-5+6(2) | | x+0.15=100 | | 2n^3+3n^2= | | 10x-(x+7)=-34 | | y=1000000-50000(20) | | 3k-2=-2k-4 | | 2f=12x-1 | | -9x+3x+18-8x= | | 5(x+4)=2(x-5) | | 2m=-5+6(1) | | 5b+54=130 | | 11=9-h | | p^2-6p+9=99 | | 7n+18=-6-n | | 32-9n=40 | | 92=82+16 | | 26x+13=5(5x+5) | | x-1=-73-5x | | 57=0.11q+0.14(q-500) | | -(6y+z-6)= | | 8r-2=8r-9-r | | 893=25g+43 | | 2(5x+4)-3= | | -2(x+1)-6=2(6x-2)+3 | | 10+X+2x=-2 | | y=10+4x | | 0.05x-1.8=0.02x-1.2 | | -444=120+6t | | 4x-7x+4=x-4+8 |